Diskresi Hakim terhadap Kekosongan Hukum Perkara Wasiat Wajibah Ditinjau dari Yurisdiksi Voluntair: Studi Empiris di Pengadilan Agama Kabupaten Kediri - Annisa Vika Ayu Nurwulan (Prodi Hukum Ekonomi Syariah (Muamalah), 2025)
The study focuses on analyzing the legal reasoning and judicial discretion in accepting and adjudicating compulsory will cases filed voluntarily, particularly in the absence of formal procedural regulations. This is an empirical research using a qualitative approach. Data were obtained through case analysis of Decision No. 007/Pdt.P/2022/PA.Kab.Kdr, interviews with judges, and supporting documentation. Data collection techniques included observation, in-depth interviews, and document study, which were then analyzed using descriptive qualitative analysis. The findings show that judges accepted the petition based on evidence of legal adoption proven through documents and witness testimony. The judges referred to Article 49 letter (b) of Law No. 3 of 2006, and Articles 171 (h) and 209 of the Compilation of Islamic Law (KHI) as legal bases. Judicial discretion was exercised to address procedural legal gaps by relying on voluntary jurisdiction principles and the concept of maslahah (public benefit). The study concludes that, in the absence of specific formal regulations, judicial discretion plays a crucial role in ensuring legal certainty, justice, and protection of rights in compulsory will cases.